The Influence of Policy Implementation and Coordination on Achieving the Stunting Reduction Target in Cianjur Regency (Study in Campaka, Naringgul, and Tanggeung Districts) - Cepi Hanapia; Kamal Alamsyah; Yaya Mulyana Abdul Aziz (Sean Institute, 2026)
This study aims to analyze the influence of policy implementation and coordination between stakeholders on achieving the stunting reduction target in Cianjur Regency, with a focus on Campaka, Naringgul, and Tanggeung Districts. The problem of stunting remains a strategic issue in health development, so effective policy implementation and optimal coordination between local governments, health workers, and other relevant parties are needed. This study uses a quantitative approach with a descriptive verification method. The results show that policy implementation and cross-sectoral coordination have generally been running well and have a very important role in achieving the stunting reduction target. Clarity of policy objectives, availability of resources, and the attitude and commitment of implementers are the main factors in successful implementation, while effective coordination through communication, division of labor, and unity of action can create synergy between sectors. Both partially and simultaneously, these two variables have been proven to have a significant and complementary influence in supporting the success of the program. However, target achievement has not been fully optimized due to ongoing obstacles such as limited access to services, socio-cultural factors, and the suboptimal integration and involvement of all stakeholders. Therefore, ongoing strengthening is needed to ensure the program runs more effectively and sustainably.